KEJENUHAN DI KALANGAN GURU BIMBINGAN DAN KONSELING DI SMAN PROVINSI RIAU - Riswani Riswani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
Guidance and Counseling teachers always required understanding the conditions and situation of students with a vengeance and so that required intense emotional involvement. Intense emotional involvement can lead to job stress and stress is ignored if the condition will potentially lead to burnout in the works. This study tries to find out the burnout of the picture and the factors that affect the burnout of the BK teachers, 23 respondents who have a lot of student guidance. Determination of the respondents using the technique of